INFORMATION SYSTEM FOR SERVICE PORTFOLIO FORMATION FOR INFOCOMMUNICATION PROVIDERS (Computer systems and information technologies, 2025)
This paper addresses the challenge of service portfolios formation for infocommunication service providers. A comprehensive analysis of existing approaches enabled the formulation of the problem within the framework of contemporary business models and underscored the necessity of developing new effective methods. These methods must reflect the specifics of interaction between IT companies, service providers, and end users, as well as the inherent characteristics of services and their delivery environments. The paper substantiates the choice of methodological foundations underlying the proposed system for service portfolio formation. The formal problem is categorized as a nonlinear, multicriteria Boolean programming task. Growing demands for alignment between service packages and user needs, coupled with the resource constraints of modern IT infrastructures and the complexity of inter-service dependencies, highlight the need to solve large-scale optimization problems. To address this, a hybrid method is proposed, combining problem decomposition into subproblems, the application of metaheuristic techniques for their resolution, and heuristic procedures for integrating partial solutions. The paper presents experimental results demonstrating the effectiveness of the proposed approach. Additionally, it outlines system-level design solutions that support the development and implementation of the information system for service portfolio formation.
Keywords: service portfolio; infocommunication service provider; service portfolio formation model; multicriteria optimization; metaheuristic methods; information system